Food Safety Knowledge of Food Sanitation Hygiene Practices in the Era of Pandemic COVID-19 - Dwi Yunita Haryanti; Yeni Suryaningsih (Universitas Muhammadiyah Jember, 2021)
Background and Objectives: Food hygiene and sanitation in various food industries or processed food service providers requires special attention from the government during this pandemic, where the sector remains a necessity for the entire community. Monitoring and evaluation are urgently needed in order to break the chain of transmission and eliminate the risk of contamination of food during processing or during packaging. This study was conducted to determine the relationship between knowledge and food hygiene and sanitation practices at public facilities providing processed food.Methods: This research is an observational study using a cross sectional design. The population in this study is the food service industry of class A2 and A3. Determination of respondents in this study was done by purposive sampling. The instrument used in this study was a questionnaire from FAO related to policies regarding the impact of COVID-19 on food safety and nutrition.Results: The results showed that the knowledge of the majority of food handler and presenters was 18 (47.4%) and the application of food hygiene and sanitation was also low 28 (73.8%). Food handlers and presenters with good knowledge have better compliance in implementing food hygiene and sanitation compared to food handlers and presenters who have sufficient and less knowledge (p value 0.05).Conclusions and Implications: Low knowledge of food handlers and presenters is known to be one of the factors not implementing food hygiene and sanitation so that it has the potential to increase the spread of the SAR-CoV-2 virus. One strategy that can be done is to provide continuous socialization and education through various mass media using a cultural approach. Keywords: Hygiene; Sanitation; Food; Pandemic.